Evaluation Of Growth Performance in Soyabean Meal Supplimentation to Catla Catla Fingerlings - P. Dhiravidaselvi, R. Ravichandran (International Journal of Modern Agriculture, 2021)
An experiment was conducted to determine the growth performance of Indian Major Carp Catla catla, fingerlings for period of 60 days. In the present study to investigate the effects of soya bean on growth performance and survival in common carp (Catla catla). Soyabean was incorporated into diets at concentrations of 1%, 2%, or 3%. The control diet contained no supplement. Soyabean at 3% produced the best and statistically significant (p<0.05) weight gain. In general, Soyabean produced better growth than 1% and 2% supplementation. The present investigation shows that incorporation of soyabean in diets for common carp results in increased growth rate. Soyabean diet was most effective in stimulating fish growth.